Tourism writing : a new literary genre unveiling the history, mystery, and economy of places and events - Palmer, Mary S. (Boca Raton : Boca Raton : Universal Publishers, 2018)
"In this era of advanced technology keeping students' attention often becomes difficult. Teachers need to find new ways to create interest. In writing classes, choosing a topic that involves students is a priority. A new genre, Tourism Writing, is an innovative and effective means of teaching students composition. It can fill this need. Tourism Writing focuses on a particular place or event, provides photos and information on nearby points of interest, and directly invites visitors. This book provides an understanding of how Tourism Writing benefits people in all areas of life. This transfers to classroom assignments when students are asked to write a poem in this genre and they are given lists of possible topics, but they also have the option to choose their own place or event. It becomes a learning experience as many are amazed at their ability to write a poem and intrigued by the history they learn while researching and they treasure their photos used for illustration. Such poems were entered in the annual Poetry Writing Contest at Faulkner University. In the process, students' communication and research skills were enhanced. They learned the history of their own area. This hands-on process is rewarding to teach. The plan is to add prose assignments on Tourism Writing to the classroom curriculum in the future. The possibilities for Tourism Writing are widespread"--
Includes bibliographical references (pages 181-186).
Keywords: Travel in literature; Travelers' writings; Travel writing; Travel in literature; Travel writing; Travelers' writings